"Loneliness can also kill:" a qualitative exploration of outcomes and experiences of the SUPERB peer-befriending scheme for people with aphasia and their significant others. Issue 18 (28th August 2022) - Moss, B.; Behn, N.; Northcott, S.; Monnelly, K.; Marshall, J.; Simpson, A.; Thomas, S.; McVicker, S.; Goldsmith, K.; Flood, C.; Hilari, K.
Abstract: Purpose: People with aphasia post-stroke are at risk for depression and social isolation. Peer-befriending from someone with similar experiences may promote wellbeing and provide support. This paper explored the views of people with aphasia and their significant others about peer-befriending. Materials and methods: We conducted a qualitative study within a feasibility trial (SUPERB) on peer-befriending for people with post-stroke aphasia and low levels of distress. Of the 28 participants randomised to the intervention, semi-structured in-depth interviews were conducted with 10 purposively selected people with aphasia (at both 4- and 10-months post-randomisation) and five of their significant others (at 4-months). Interviews were analysed using Framework Analysis. Results: Participants and their significant others were positive about peer-befriending and identified factors which influenced their experience: the befrienders' personal experience of stroke and aphasia, their character traits and the resulting rapport these created, the conversation topics they discussed and settings they met in, and the logistics of befriending, including planning visits and negotiating their end. Interviewees also made evaluative comments about the befriending scheme. Conclusion: Peer-befriending was an acceptable intervention. Benefits for emotional wellbeing and companionship were reported. The shared experience in the befriending relationship was highly valued. Implications for Rehabilitation: The lived experience of stroke and aphasia of befrienders was highly valued by people with aphasia receiving peer-befriending. Training, regular supervision, and support for befrienders with practicalities such as organising visits ensured the befriending scheme was perceived as straightforward and acceptable by befriendees. Those receiving peer-befriending would recommend it to others; they found it beneficial, especially in terms of emotional wellbeing and companionship.